Lentinus edodes Exposure before and after Fetus Implantation: Materno-Fetal Development in Rats with Gestational Diabetes Mellitus - Laurino, Leticia F.; Viroel, Fabia J. M.; Caetano, Erika; Spim, Sara; Pickler, Thaisa B.; Rosa-Castro, Raquel M.; Vasconcelos, Edilma Albuquerque; Jozala, Angela F.; Hataka, Alessandre [UNESP]; Grotto, Denise; Gerenutti, Marli (Mdpi, 2019)
Background: The presence of beta-glucans and phenolic compounds in Lentinus edodes suggests this mushroom can be used as a nutritional supplement. Two gestational conditions (before and after fetus implantation) were evaluated, and Lentinus edodes exposure was performed in diabetes mellitus rat model induced by streptozotocin in pre-clinical tests. Methods: On the 20th day of pregnancy, cesarean sections were performed. Blood was collected for biochemical, hematologic parameters and oxidative stress biomarkers. Placenta and amniotic fluid were collected, and fetuses were analyzed through morphological evaluation. Results: The mushroom did not reduce the severe hyperglycemia of the mother-concept but promoted an increase in maternal insulin levels; reduced the levels of alanine aminotransferase, and aspartate aminotransferase, triglyceride and total cholesterol; protected the animals from post-implantation losses. Liver damage induced by streptozotocin was reversed in experimental groups. Conclusions: Lentinus edodes mushroom has antioxidant properties that can minimize the damage caused by gestational diabetes mellitus.
Keywords: Lentinus edodes; mushroom nutraceuticals; gestational diabetes mellitus; anti-diabetic activity; pre-clinical study